Educational Recovery in the Aftermath of the Pandemic: A Critical Analysis of Recovery Policies across Canada - Volante, Louis; Klinger, Don A.; Lara, Camila (Canadian Journal of Education / Revue canadienne de l'éducation)

(untitled) (Canadian Society for the Study of Education, 2024)
This study expands on our previous research focusing on provincial educational policies to support students’ academic resilience during the pandemic, with the current focus being on the “recovery phase” of the pandemic (January 2022 to December 2023). Our analysis identified 46 provincial documents that addressed one or more of the three dimensions of academic resilience during this recovery period. Similar to our previous findings, a greater emphasis was placed on academic outcomes. There was an increased focus on mental health, while much less attention was paid to physical health and well-being. While we identified examples of provinces that dedicated resources and funding to support these dimensions, we argue the policies implemented during the recovery phase will require more conviction to address the negative long-term impacts of the pandemic, particularly for disadvantaged students, and that such efforts will likely need to continue beyond public schooling.